Flash-Based Flash-Based Mathematics Learning Media Case Study At Randugunting State Primary School Semarang District - Nova Dwi Putra; Agus Priyadi (University of Science and Computer Technology, 2023)
Elementary School (SD) is the initial level of formal education implemented in Indonesia which takes 6 years. Elementary school students are generally aged between 7-12 years, at this stage the knowledge taught is basic knowledge which will then continue to be developed until middle school and high school. The lecture method used by schools in general and the use of companion books that are less interesting result in students being less able to understand Mathematics subjects, especially Flat Figures. The design of this learning media is to provide a solution for teaching Mathematics for fourth grade elementary school students in an easier and more enjoyable way. The problem faced here is how to design interactive learning media as an alternative learning media to support the teaching and learning process in schools for class IV elementary school that is easy to understand materially and makes it easier for students to see real things or objects. The method used is Research and Development (R&D). In connection with the problems being studied and preparations for formulating a research framework, at this stage, data collection is carried out by means of observation and interviews, then thinking about the product that will be produced by formulating research objectives, after that determining product specifications and making a research schedule for developing the initial form of the product. What will be produced is suitable for analyzing students' values and interests. The next step is to carry out initial field trials on a limited scale by validating the expert team to test whether the product is feasible or not. If it is not feasible, improvements will be made to the initial product produced. The manifestation of this research and design is an interactive multimedia learning CD. The overall results achieved are expected to increase added value to assist educators in providing interesting, fun and easy to understand mathematics education to improve the learning achievement of class IV students at Randugunting Public Elementary School, Semarang Regency.